Contact sheets. On the photographic enunciation - Mangano, Dario (E|C, 2020)
The contribution analyzes the photographic tryouts to investigate the photographic production. Usually considered outside the text, the tryouts can instead be real texts that allow you to observe the way in which the relationship between enunciator and enunciatee is inscribed in the act of photographic enunciation.